Early treatment with captopril after acute myocardial infarction. Issue 3 (March 1993) - Ray, S G; Pye, M; Oldroyd, K G; Christie, J; Connelly, D T; Northridge, D B; Ford, I; Morton, J J; Dargie, H J; Cobbe, S M
Abstract : OBJECTIVES--To determine the effects of early treatment with captopril on haemodynamic function, neuroendocrine biochemistry, left ventricular structure, clinical outcome, and exercise capacity over one year from acute myocardial infarction. DESIGN--Randomised, double blind, placebo controlled comparison of captopril and placebo. SETTING--Coronary care units and cardiology departments of two university teaching hospitals in Glasgow. PATIENTS--99 haemodynamically stable patients with acute myocardial infarction, selected on clinical grounds as being at risk of late ventricular dilatation. INTERVENTION--Captopril or identical placebo started between six and 24 hours after start of symptoms and continued for 12 months. Target maintenance dose was 25 mg three times a day. MAIN OUTCOME MEASURES--(a) Acute haemodynamic effects of treatment; (b) neuroendocrine biochemistry from admission to two months; and (c) change in echocardiographic measures of left ventricular size, clinical outcome, and exercise capacity after 12 months of treatment with a separate analysis of the effects of one month of treatment withdrawal on left ventricular volumes. RESULTS--Captopril caused acute reductions in mean (SEM) pulmonary artery pressure (2.48 (0.69) mm Hg) and systemic vascular resistance (260 (103)) dyn.s.cm-5). Over the first 10 hours captopril reduced mean arterial pressure by 12.1 (2.4) mm Hg compared with 3.8 (1.9) mm Hg in the placebo group. No patient had to be withdrawn from the captopril group because of hypotension. From day 1 onwards systolic and diastolic arterial pressures in the captopril treated group were slightly but not significantly lower than on placebo. There was no difference in the incidence of ventricular or supraventricular arrhythmia with treatment. Captopril prevented the day 3 peak in angiotensin II that occurred in the placebo group (peak concentration (interquartile range): 10.1 (4.8-19.4) pg/ml v 16.8 (4.3-46.3) pg/ml)) but had no effect on atrial natriuretic factor, arginine vasopressin, or catecholamines. Plasma atrial natriuretic factor remained above normal in both groups at two months after infarction. After one year left ventricular volume indices had increased less on captopril than on placebo: left ventricular end systolic volume index 5.4 ml/m2 v 14.7 ml/m2 (95% confidence interval (95% CI) of difference -14.6 to -3.9; p = 0.0011); left ventricular end diastolic volume index 8.4 ml/m2 v 19.0 ml/m2 (95% CI of difference, -17.0 to -4.2; p = 0.0016). Withdrawal of captopril for one month did not affect ventricular volumes. There was no difference in exercise capacity. CONCLUSIONS--Captopril started between six and 24 hours after acute myocardial infarction is not associated with significant hypotension. It suppresses activation of the renin angiotensin system but has no effect on plasma concentrations of other neurohormones. Atrial natriuretic factor remains raised at two months after myocardial infarction. Captopril significantly decreases left ventricular dilatation. This effect is not lost after one month of treatment withdrawal and is thus due to an alteration of left ventricular structure and not to a short lived haemodynamic action of captopril. Long-term treatment with captopril does not result in improved aerobic exercise capacity after acute myocardial infarction.